Results from the Chinese Taipei (Taiwan) 2022 report card on physical activity for children and youth - Chen-Kang Chang; Ching-Lin Wu (Elsevier, 2023)
Background /Objective: In Taiwan, physical inactivity is highly prevalent among children and adolescents. Chinese Taipei (Taiwan) joined the Global Matrix 3.0 in 2018 to share local data on childhood physical activity and related factors with the international community. This study reports the grades for 10 indicators endorsed by the Global Matrix 4.0 and 1 additional indicator. Methods: Local data for school-aged children and adolescents (approximately 5-17 years old) from 2017 to 2022 were used to determine the grades. The data were obtained from online academic databases and websites of government agencies. The highest priority was given to national surveys, followed by studies using nationally representative samples. Results: The data revealed very poor Overall Physical Activity, Organized Sport Participation, and Active Play (F, D−, and F, respectively). Active Transportation, Sedentary Behavior, and Family and Peers were also below average (C−, D+, and D−, respectively). Taiwan's central and local governments have recognized the importance of physical activity by implementing related policy and improving public sports facilities. Accordingly, School and Community and the Built Environment both received a grade of A−, and Government Strategies and Investments received a B+. Physical Fitness received an INC for lack of data. An additional indicator, body mass index, received a grade of B−. Conclusions: Despite great effort by governments and schools, physical activity levels are low and sedentary behavior is prevalent among Taiwanese children and adolescents.